Tourist in the (K)Now: social Rapportage and the performative rapport of social media. Issue 3 (2nd September 2019) - Savage, Karen
ABSTRACT: This paper explores how tourists, through the use of social and digital media platforms, are able to develop formations and connections that enhance a sense of rapport. The role of tourist is articulated through a new term, the 'rapporter', and the activity of the rapporter takes place as 'rapportage'. Additionally, I suggest that this is achieved through the availability of mobile Apps. I propose that through the process and act of rapportage individuals can disseminate their responses to events and experiences, which provides an opportunity for further rapport. The voices then become part of a collective rapport inspired to understand and connect with others and can provide different examples compared to the divisive and often aggressive reporting frequently articulated as part of the 'post-truth' environment.